A Green Approach to Obtaining Glycerol Carbonate by Urea Glycerolysis Using Carbon-Supported Metal Oxide Catalysts - Karolina Ptaszyńska; Anna Malaika; Klaudia Kozigrodzka; Mieczysław Kozłowski (Molecules, 2023)
The results of sustainable and selective synthesis of glycerol carbonate (GC) from urea and glycerol under ambient pressure using carbon-fiber-supported metal oxide catalysts are reported. Carbon fibers (CF) were prepared via a catalytic chemical vapor deposition method (CCVD) using Ni as a catalyst and liquefied petroleum gas (LPG) as a cheap carbon source. Supported metal oxide catalysts were obtained by an incipient wetness impregnation technique using Zn, Ba, Cr, and Mg nitrates. Finally, the samples were pyrolyzed and oxidized in an air flow. The obtained catalysts (10%MexOy/CFox) were tested in the reaction of urea glycerolysis at 140 °C for 6 h under atmospheric pressure, using an equimolar ratio of reagents and an inert gas flow for NH3 removal. Under the applied conditions, all of the prepared catalysts increased the glycerol conversion and glycerol carbonate yield compared to the blank test, and the best catalytic performance was shown by the CFox-supported ZnO and MgO systems. Screening of the reaction conditions was carried out by applying ZnO/CFox as a catalyst and considering the effect of reaction temperature, molar ratio of reagents, and the mode of the inert gas flow through the reactor on the catalytic process. Finally, a maximum yield of GC of about 40%, together with a selectivity to glycerol carbonate of ~100%, was obtained within 6 h of reaction at 140 °C using a glycerol-to-urea molar ratio of 1:1 while flowing Ar through the reaction mixture. Furthermore, a positive heterogeneous catalytic effect of the CFox support on the process was noticed.